2018
DOI: 10.1186/s40168-018-0513-5
|View full text |Cite
|
Sign up to set email alerts
|

Fine metagenomic profile of the Mediterranean stratified and mixed water columns revealed by assembly and recruitment

Abstract: BackgroundThe photic zone of aquatic habitats is subjected to strong physicochemical gradients. To analyze the fine-scale variations in the marine microbiome, we collected seven samples from a single offshore location in the Mediterranean at 15 m depth intervals during a period of strong stratification, as well as two more samples during the winter when the photic water column was mixed. We were able to recover 94 new metagenome-assembled genomes (MAGs) from these metagenomes and examine the distribution of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
156
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(175 citation statements)
references
References 108 publications
19
156
0
Order By: Relevance
“…Recently, we characterized variations in the marine microbiome at different depths within the photic zone during a period of strong thermal stratification of the water column (Haro‐Moreno et al, ). Results showed that marine Thaumarchaeota were only found below the deep chlorophyll maximum (accounted for up to 10% of the community at 90 m), coinciding with the increase of available ammonia that is practically non‐existent at shallower depths.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we characterized variations in the marine microbiome at different depths within the photic zone during a period of strong thermal stratification of the water column (Haro‐Moreno et al, ). Results showed that marine Thaumarchaeota were only found below the deep chlorophyll maximum (accounted for up to 10% of the community at 90 m), coinciding with the increase of available ammonia that is practically non‐existent at shallower depths.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we screened publicly available metagenomes using ribosomal protein sequences of the previously reconstructed UAP2 MAGs and assembled and binned UAP2-positive samples yielding six additional MAGs belonging to the UAP2 lineage ( Table 1, Supplementary Tables 1-2 , see Methods for details). Four of the newly assembled MAGs were recovered from metagenomes of a groundwater aquifer located adjacent to the Colorado River 42 , while the two others as well as six previously reconstructed MAGs, derived from metagenomes of marine waters in the Atlantic 41,43 and Indian Oceans 44 as well as the Mediterranean Sea 45 ( Supplementary Table 2 ). UAP2 representatives were detected in samples from various depths in the water column (85-5000 m), fluctuating oxygen conditions (anoxic to oxic) and temperatures (sampling sites had temperatures from 18 up to 106°C) ( Supplementary Figure 1, Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Scaffolds predicted to infect Proteobacteria were among the most abundant in all depths with abundances ranging from 0.5% to 2.4% of mapped reads. Previous investigation of the metagenomes from the cellular fraction revealed shifts in taxonomic composition of prokaryotic communities throughout the depth gradient [8]. These were dominated, at all depths, by Proteobacteria, mostly from the classes Alphaproteobacteria and Gammaproteobacteria.…”
Section: Viral Community Compositionmentioning
confidence: 89%
“…In response, viruses adapt to those changes to guarantee their survival. The depth gradient of stratified water masses displays marked changes in environmental conditions mainly driven by light availability and temperature [8]. Thus it is an ideal habitat to study associations between environmental parameters, viruses, and their hosts.…”
Section: Introductionmentioning
confidence: 99%